1991
DOI: 10.1080/09602019108520163
|View full text |Cite
|
Sign up to set email alerts
|

Auditory feedback for walking difficulties in a case of unilateral neglect: A pilot study

Abstract: A 29-year-old woman with left sensory neglect, visual neglect, and frontal lobe difficulties presented problems in physiotherapy because she walked with her left foot heel-up in a highly unstable plantarflex position. She completely failed to learn to lower her heel on walking, which as a result could have led to an eversion injury, despite the fact that she could lower her heel to the floor on command. A pressure-sensitive switch attached to a buzzer on her belt was inserted under her left heel, and a walking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…To date, there are few reports of walking training for USN patients. Robertson and Cashman (1991) performed walking exercise using auditory feedback in order to make the paretic lower limbs aware for patients with USN with foot drop, and reported that patients became more focused on the paretic lower limb during walking. However, this study did not focus on visuospatial cognition.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are few reports of walking training for USN patients. Robertson and Cashman (1991) performed walking exercise using auditory feedback in order to make the paretic lower limbs aware for patients with USN with foot drop, and reported that patients became more focused on the paretic lower limb during walking. However, this study did not focus on visuospatial cognition.…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical perspective, the last of these, tactile neglect, may be the most salient manifestation of a lateralized attentional impairment, since a lack of awareness of tactile stimuli on the contralesional side may hinder rehabilitative interventions based on body awareness (e.g. Robertson and Cashman, 1991). On the other hand, directing patients' attention to the affected side may reduce the extent of tactile neglect (Weiskrantz and Zhang, 1987).…”
Section: Introductionmentioning
confidence: 99%